ERBB2 Mutations as Potential Predictors for Recurrence in Colorectal Serrated Polyps by Targeted Next-Generation Sequencing - Wang, Qi-Wen; Wang, Xin-Yuan; Zhang, Qing-Wei; Chen, Jin-Nan; Zhou, Yu-Jie; Tang, Zhao-Rong; Wang, Rui-Lan; Chen, Haoyan; Chen, Huimin; Li, Xiao-Bo (Frontiers in Oncology, 2022)
Background Follow-up guidelines for serrated polyps (SPs) are mainly based on factors such as histology and size with limited evidence. The underlying genomic mechanism of SPs in relation to recurrence risks is utterly unknown. Methods We applied targeted next-generation sequencing (NGS) approach on two groups of SPs [polyp-relapsed SPs (PRSPs) vs. polyp-free SPs (PFSPs)] based on the surveillance outcomes to compare differences of DNA variants in 71 colorectal cancer-associated genes. A multicenter validation cohort was established longitudinally from 2016 to 2019 to confirm the relevant results. Results Among the 96 NGS samples, at least one mutant after filtration was detected in 90 samples (94%). Molecular profiling presented BRAF, KRAS, and APC as top 3 mutated genes. FBXW7, MSH2, and ERBB2 might be recurrence-relevant, while DMD, BRCA1, and BRCA2 might be negatively correlated with recurrence. Notably, ERBB2 mutants (R678Q and V842I) (n = 5) had higher risks of polyp recurrence than the wild types (n = 85), with a median polyp-free interval of 15 months compared to 26 months [P < 0.001; hazard ratio (HR) = 4.9; 95% confidence interval (CI) = 1.9–12.8]. Furthermore, a multicenter cohort composed by 321 SPs verified that ERBB2-mutated SPs had increased risks of polyp recurrence (P < 0.001; HR = 3.7; 95% CI = 2.3–6.0) and advanced neoplastic lesion (ANL) recurrence (P < 0.001; HR = 10.0; 95% CI = 2.7–36.9) compared with wild-type SPs, respectively. Conclusions Our results are emphasizing that SP individuals with ERBB2 mutants are at higher risks of subsequent colorectal neoplasms. ERBB2 mutants might work as facilitated markers for prediction of high-risk SPs and might implicate a potential mechanism in the serrated pathway to colorectal carcinoma (CRC).